Organizing and supporting cultural activities by local government with the example of the City of Lublin - Suchodolski, Bartłomiej (Management and Administration Journal, 2023)
Conducting cultural activities is the compulsory task of local government. Implementation of this task may be realized by organizing and supporting such activities. Local governments organize cultural activities particularly through their subordinate institutions of culture. Supporting cultural activities can take the form of grants, awards and scholarships. To realize all these activities, the local government has to allocate an appropriate amount of money in the budget. This article presents the problem of organizing and supporting cultural activities with the example of the City of Lublin.